Da transferência de suporte ao sistema de informação organizacional: um posicionamento urgente e estratégico - Maria Manuela Gomes de Azevedo Pinto (2011)
Since the late 90's that digitization has assumed a growing importance considering of traditional techniques such as microfilming and photography, and increasingly conquering users e professional that also benefiting from attractive financing options, either within the Digital Cultural Heritage, or in the dematerialisation process at organizations or public and private institutions. However, digitization, and is no longer just a means to create digital reproductions of physical objects, facilitating access and support when preserving the "analog" original or solving problems of lack of storage space. It means in fact the production of digital information and as any kind of digital information should be effectively and efficiently produced, managed, stored, distributed, used and preserved. Digitization is therefore a process that requires planning, which involves a cycle of management, which entails risks, which have a profound impact on the activities, the skills of the involved actors, on the designed work flows, on the technology platform, on the organizational information system, reaching the organizational structures and the improvement and development of "innovative business models", presenting itself as an insurmountable challenge in terms of information management, particularly with regard to the preservation of information in digital media and their assumption in a integrated prospective, in a systemic, systematic and active way.